Colposcopic assessment by Swedescore, evaluation of effectiveness in the Swedish screening programme: a cross‐sectional study. (30th December 2021) - Alfonzo, Emilia; Holmberg, Erik; Milsom, Ian; Strander, Björn
Abstract: Objective: To evaluate the effectiveness and performance of Swedescore in the Swedish screening programme. Design: Cross‐sectional register study. Setting and Population: All Swedish women aged over 18 years with a colposcopic assessment linked to a biopsy in the Swedish National Cervical Screening Registry, 2015–20. Methods: Colposcopies with Swedescore were compared with the histopathological diagnosis of cervical intraepithelial neoplasia grade 2 or higher (CIN2+). The respective influence of cytology and human papillomavirus (HPV) testing, at referral for colposcopy and concurrently with colposcopy, were investigated in regression models. Main Outcome Measures: CIN2+. Results: A total of 11 317 colposcopic assessments with Swedescore were included. Odds ratios for CIN2+ increased for every step in the Swedescore scale. At Swedescore ≥0–1, the proportion of CIN2+ was 9.8%. At Swedescore ≥8, the specificity was 93.3% and the positive predictive value was 60.1%, Area under the receiver operating characteristics curve (AUC) was 0.71. If the smear had been abnormal at referral, a normal colposcopy (Swedescore 0–1) was still associated with a CIN2+ risk of more than 5%. In the regression model, cytology and HPV had higher odds ratio for CIN2+ than colposcopy; the combination resulted in an AUC of 0.88. Conclusions: Swedescore works well in a routine clinical setting but colposcopy assessed with Swedescore was inferior to that reported in previous clinical studies. No safe cutoff level was identified for refraining from biopsy. See‐and‐treat at Swedescore 8–10 is feasible only if referral cytology showed high‐grade squamous intraepithelial lesion. Tweetable Abstract: No safe cutoff level for refraining from biopsy nor for see‐and‐treat with Swedescore. Tweetable abstract: No safe cutoff level for refraining from biopsy nor for see‐and‐treat with Swedescore. Linked article: This article is commented on by Margaret Cruickshank, pp. 1268 in this issue. To view this minicommentary visit https://doi.org/10.1111/1471-0528.17055 .